2009
DOI: 10.1167/9.7.14
|View full text |Cite
|
Sign up to set email alerts
|

Perceived duration of visual motion increases with speed

Abstract: Despite wide recognition that a moving object is perceived to last longer, scientists do not yet agree as to how this illusion occurs. In the present study, we conducted two experiments using two experimental methods, namely duration matching and reproduction, and systematically manipulated the temporal frequency, spatial frequency, and speed of the stimulus, to identify the determinant factor of the illusion. Our results indicated that the speed of the stimulus, rather than temporal frequency or spatial frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
192
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(219 citation statements)
references
References 29 publications
24
192
1
2
Order By: Relevance
“…However, the impact of effort on perceived duration need not be experiential, as stimuli that allude to motion, action, or exertion also elongate perceived durations. For example, faster moving non-biological stimuli are perceived to last longer than slower moving stimuli (Brown, 1995;Kaneko & Murakami, 2009), and the perceived duration of images of ballet dancer statues are lengthened when the poses reflected greater levels of exertion (Nather, Bueno, Bigand & Droit-Volet, 2011). The elongation of subjective time as a result of effort are also found for mental activity.…”
Section: Effort Disrupts Implicit Agencymentioning
confidence: 98%
“…However, the impact of effort on perceived duration need not be experiential, as stimuli that allude to motion, action, or exertion also elongate perceived durations. For example, faster moving non-biological stimuli are perceived to last longer than slower moving stimuli (Brown, 1995;Kaneko & Murakami, 2009), and the perceived duration of images of ballet dancer statues are lengthened when the poses reflected greater levels of exertion (Nather, Bueno, Bigand & Droit-Volet, 2011). The elongation of subjective time as a result of effort are also found for mental activity.…”
Section: Effort Disrupts Implicit Agencymentioning
confidence: 98%
“…The idea that the rate of accumulation is greater for slower-moving stimuli is perhaps counter-intuitive, and runs against the typical assertion that faster stimuli seem to last longer (Beckmann & Young, 2009;S. W. Brown, 1995;Kaneko & Murakami, 2009). However, there is some evidence that the relationship between speed and perceived duration is not uniformly positive (Predebon, 2002).…”
Section: The Effects Of Changes In Speed On Judgements Of Durationmentioning
confidence: 98%
“…Stimulus speed has been argued to affect the pacemaker, with faster speeds producing higher accumulation rates and longer subjective time (Kaneko & Murakami, 2009). …”
Section: Time Winding Down: How Do Changes In Speed Affect the Percepmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that a moving stimulus is perceived to last longer in duration than a slower or stationary stimulus of the same physical duration, a phenomenon referred to as subjective time dilation (4)(5)(6)(7)(8)(9). Some researchers proposed that this subjective time dilation effect might reflect a result of long-term evolutionary adaptation (6,10).…”
mentioning
confidence: 99%